2008
DOI: 10.1089/sur.2007.031
|View full text |Cite
|
Sign up to set email alerts
|

Review of Community-Referred Hand Infections

Abstract: Hand infections are surgical emergencies; correct and prompt management thus is essential. A quick and effective regimen for treatment yielded good results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
(9 reference statements)
1
2
0
2
Order By: Relevance
“…The most frequently isolated microorganism in our study (30% of cases) was MRSA, similar to most other articles on hand infections (Anwar, Tzafetta & Southern, 2008; Brown & Young, 1993; Eaton & Butsch, 1970; McDonald et al, 2011; Nunley et al, 1980). Fowler & Ilyas’s (2013) report on 1,507 incision and drainage patients showed 53% of the cases were due to MRSA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most frequently isolated microorganism in our study (30% of cases) was MRSA, similar to most other articles on hand infections (Anwar, Tzafetta & Southern, 2008; Brown & Young, 1993; Eaton & Butsch, 1970; McDonald et al, 2011; Nunley et al, 1980). Fowler & Ilyas’s (2013) report on 1,507 incision and drainage patients showed 53% of the cases were due to MRSA.…”
Section: Discussionsupporting
confidence: 90%
“…Anwar, Tzafetta & Southern (2008) also reported that majority of infections were cellulitis and abscess. In our study, the majority of patients had cellulitis and deep abscess, there were no patients with paronychia, and there were 2 felon patients (Table 3).…”
Section: Discussionmentioning
confidence: 97%
“…There are few recent reports on the epidemiology of patients presenting with acute hand infections [1, 3]. Anwar and colleagues published the results of a retrospective chart review with data from 76 patients with hand infections admitted to the plastic surgery unit at a general hospital in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…genannt, welche in ihren Studien durchgängig S. aureus als führenden Keim, zumeist in über 50 % der Fälle isolieren konnten [2,5,6]. Während in einigen Studien, insbesondere aus dem nordamerikanischen Raum, das Vorkommen von Methicillin-resistentem-Staphylococcus-aureus (MRSA) mit teilweise über 50 % als relativ hoch zu bewerten ist [7][8][9][10][11], dokumentieren andere Studien aus dem europäischen Raum ein deutlich geringeres Vorkommen von MRSA [2,12]. Gleichzeitig ist jedoch auch in Europa eine steigende Prävalenz von MRSA zu beobachten -dies aber insbesondere bei nosokomialen Infektionen [13].…”
Section: Keimspektrumunclassified
“…Die Autoren dieses Beitrags konnten in der rezenten Literatur nur 2 Studien zur Resistenzlage bei klinischen Infektionen der Hand ausmachen: Sowohl Anwar und Mitarb. [12] als auch Fuchsjäger und Mitarb. [2] konnten in ihren Fallserien mit 76 respektive 204 Patienten eine gute Wirksamkeit der üblicherweise eingesetzten (und empfohlenen) Antibiotika nachweisen [25,26].…”
Section: Antibiotikatherapieunclassified